1998
DOI: 10.1016/s0014-5793(98)00222-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein kinase C‐mediated phosphorylation of the short cytoplasmic domain isoform of C‐CAM

Abstract: C-CAM is a ubiquitously expressed cell adhesion molecule belonging to the carcinoembryonic antigen family. Two co-expressed isoforms, C-CAM-L and C-CAM-S, are known, having different cytoplasmic domains both of which can be phosphorylated in vivo. Here we have characterized the PKCmediated phosphorylation of the short cytoplasmic domain isoform, C-CAM-S. Phorbol myristyl acetate induced phosphorylation of C-CAM-S in transfected CHO cells. Using synthetic peptides and Edman degradation we identified Ser RRW as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…We further conclude that the direct interaction of CEACAM1-4S with actin is physiologically important, and that CEACAM1-4S is a major effector in the cytoskeletal rearrangements required for lumen formation in this model. CEACAM1-4S reveals the presence of Thr 457 and Ser 459 , residues that have been previously shown to be phosphorylated in murine CEACAM1 and predicted to be phosphorylated in human CEACAM1 (35). To demonstrate that these residues are phosphorylated in human CEACAM1, CEACAM1-4S-transfected MCF7 cells were grown in three-dimensional culture with or without 32 P i , cells were harvested and lysed, CEACAM1 was immunoprecipitated and proteins run on SDS gels, and the gels probed for 32 P by autoradiography or Western blotting with anti-phospho-Ser/Thr antibodies.…”
Section: Confocal Analysis Of Wild-type and Mutant Ceacam1-4s-actinmentioning
confidence: 88%
“…We further conclude that the direct interaction of CEACAM1-4S with actin is physiologically important, and that CEACAM1-4S is a major effector in the cytoskeletal rearrangements required for lumen formation in this model. CEACAM1-4S reveals the presence of Thr 457 and Ser 459 , residues that have been previously shown to be phosphorylated in murine CEACAM1 and predicted to be phosphorylated in human CEACAM1 (35). To demonstrate that these residues are phosphorylated in human CEACAM1, CEACAM1-4S-transfected MCF7 cells were grown in three-dimensional culture with or without 32 P i , cells were harvested and lysed, CEACAM1 was immunoprecipitated and proteins run on SDS gels, and the gels probed for 32 P by autoradiography or Western blotting with anti-phospho-Ser/Thr antibodies.…”
Section: Confocal Analysis Of Wild-type and Mutant Ceacam1-4s-actinmentioning
confidence: 88%
“…Calmodulin inhibitors block the interaction of calmodulin with L-selectin and induce rapid L-selectin shedding upon treatment of neutrophils [50]. It is well established that the association of calmodulin with a number of ligands is regulated by PKC phosphorylation of the calmodulin-binding region [51][52][53]. We are currently examining whether the phosphorylation of L-selectin regulates calmodulin binding.…”
Section: Discussionmentioning
confidence: 99%
“…We first considered posttranslational changes such as phosphorylation of Thr and Ser residues. Previous work by Obrink and co-workers have shown that Thr and Ser residues in rat CEACAM1-4S can be phosphorylated by protein kinase C isozymes (Edlund et al, 1998), and recent work in our lab have shown residues Thr457 and Ser459 in human CEACAM1-4S were transiently phosphorylated during glandular lumen formation in vitro (Chen et al, 2007). To test the hypothesis that phosphorylation of these residues was responsible for the differences seen between the two model systems, we generated mutants T457D, T457A, S459D, S459A, T457D þ S459D and T457A þ S459A.…”
Section: Ceacam1 Isoforms In Lumen Formationmentioning
confidence: 98%